Augusto Boal: Theater and Romance - Cunha, Ademilson Henrique da (2011)
Augusto Boal proposes the theory about the Theater of the Oppressed by questioning the classical concepts of art, specifically those concerning the tragedy, for considering them conservative of scenery which excludes the popular manifestations. In this way, the author investigates the theatrical activities through several epochs, developing their theories, enlarging their horizons. From this, he elaborates a whole of theater techniques aiming at transforming the spectator into spect-actor by bringing him to consciousness and making him to participate of the action. This set of techniques characterizes the aesthetics known as the Theater of the Oppressed and works by means of a system called Coringa System. The Theater of the Oppressed thought, originally, for theater activities has revealed its importance to other fields. Besides its efficiency in education, politics and therapeutics activities, the Theater of the Oppressed favors the composition of Augusto Boal’s literary texts, which can be seen through the didascalias and microdescriptions.